The impact of E-HR on the roles and competencies of HR - Ngo Thi Vo, Ha (My University, 2011)
Since the emergence of the internet, a new era of HR termed as E-HRM has begun, dramatically reengineering the HR practices and processes to operate in a highly competitive market. As a result, HRM has undergone a change process in terms of HRM functions over the last decade. Observations through previous studies lead us to the interest of seeking for both positive and negative impacts of E-HR to HRM function in organizations, particularly to the changes in roles and competencies of HR specialists as well as non-HR staff (line managers and employees). This research is a qualitative single case study based on semi-structured interview conducted via phone calls. Data was collected during semi-structured interviews with 10 middle management executives including 4 HR managers and 6 other functional managers in a successful MNC in the industry of milk and dairies in Vietnam. The case company is in the first phase of strategically transforming HR department at different levels and has just adopted ICTs in recent years. There is a trend to continue the automation of HR service in the next few years. In addition, the findings suggest that the delivery of HR services with a small range of web-based tools used hardly enables the expected changes in HR’s role toward a strategic partner though it supports the shift of HR focus to the role as employee champion. The initiation of E-HRM practices is pushing HR to move from a traditional bureaucratic department to a client-friendly approach which potentially targets at the role of an employee champion. Another tangible effect caused by E-HRM is the devolvement of HR responsibilities to line management though the support from HR technology to their daily work is unobvious. However, improvements in competencies of HR professional after the implementation of E-HRM were found to be inconsiderable. A preference of developing people related skills such as communication, teamwork, consultancy and negotiation to other types of competencies existed among HR professionals, though they were suggested to focus on upgrading the business knowledge, critical thinking and leadership.
Keywords: E-HRM; HR roles; HR competencies; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|